Penerapan Nilai-nilai Pendidikan Agama Islam Untuk Meningkatkan Kecerdasan Emosional dan Kecerdasan Spiritual (ESQ) - Eny Fatimatuszuhro Pahlawati (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2021)
This study examines the application of Islamic Religious Education values ​​to improve emotional intelligence and spiritual intelligence (ESQ) for class VIII at SMP Al-Hikmah Balongrejo Sumobito Jombang. This study uses a qualitative research method using data collection methods of observation, interviews and documentation. The data analysis used was descriptive technique. The results showed that the application of Islamic Religious Education values ​​to improve emotional intelligence and spiritual intelligence had been applied by students well and quite well in everyday life, especially in the school environment. Learners have been able to control themselves when faced with problems that occur in the scope of the school, especially when receiving material in learning. Although there are still some students who have not been able to implement it, this is not a burden for educators to teach the values ​​of Islamic Religious Education to improve emotional intelligence and spiritual intelligence for class VIII at SMP Al-Hikmah Balongrejo Sumobito Jombang.